Does Government Spending Drive Regional Economic Growth? - Putri, Dwi Taruko; Azwardi, Azwardi; Marwa, Taufiq; Andaiyani, Sri (International Journal of Economics and Financial Issues, 2018)
Regional Economic Growth in Indonesia varies in each region due to differences in geographic conditions between regions. This Research related to the relationship of government spending and economic growth which is still a debate among academicians. This study aims to analyze the effect of government spending, investment and labor on regional economic growth. The method used is fixed effect method. Investments procured by domestic investment have no significant and obvious effect on economic growth in Indonesia. Government spending has a positive and significant impact on economic growth. An increase in government spending can lead to an increase in economic growth. As policy makers, the government should play an active role to stimulate the economy through countercyclical fiscal policies. The labor force has a positive effect on regional economic growth. This result shows that the worker has been absorbed so as to encourage regional economic growth. Keywords: Economic Growth, Government budget, Regional Economics JEL Classifications: H0, H50, O40, O47